Burkina Faso : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The Poverty Reduction Strategy Paper (PRSP) on Burkina Faso explains economic growth and persistence. The government intends to strengthen the foundations of macroeconomic and financial stability, and enhance competitiveness in promising sectors. Success in meeting the expected objectives of economic growth hinges on the adoption of a competitive strategy for the national economy and a refocusing of economic policies toward better-targeted actions to guarantee a better impact on beneficiary populations. Regarding improvements to the participatory process, actions were undertaken to deepen dialogue and strengthen the coordination of interventions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet